Determinants of clean birthing practices in low- and middle-income countries: a scoping review - Joanna Esteves Mills; Erin Flynn; Oliver Cumming; Robert Dreibelbis (BMC, 2020)
Abstract Background Infection is a leading cause of maternal and newborn mortality in low- and middle-income countries (LMIC). Clean birthing practices are fundamental to infection prevention efforts, but these are inadequate in LMIC. This scoping study reviews the literature on studies that describe determinants of clean birthing practices of healthcare workers or mothers during the perinatal period in LMIC. Methods We reviewed literature published between January 2000 and February 2018 providing information on behaviour change interventions, behaviours or behavioural determinants during the perinatal period in LMIC. Following a multi-stage screening process, we extracted key data manually from studies. We mapped identified determinants according to the COM-B behavioural framework, which posits that behaviour is shaped by three categories of determinants - capability, opportunity and motivation. Results Seventy-eight studies were included in the review: 47 observational studies and 31 studies evaluating an intervention. 51% had a household or community focus, 28% had a healthcare facility focus and 21% focused on both. We identified 31 determinants of clean birthing practices. Determinants related to clean birthing practices as a generalised set of behaviours featured in 50 studies; determinants related specifically to one or more of six predefined behaviours - commonly referred to as "the six cleans" - featured in 31 studies. Determinants of hand hygiene (n = 13) and clean cord care (n = 11) were most commonly reported. Reported determinants across all studies clustered around psychological capability (knowledge) and physical opportunity (access to resources). However, greater heterogeneity in reported behavioural determinants was found across studies investigating specific clean birthing practices compared to those studying clean birthing as a generalised set of behaviours. Conclusions Efforts to combine clean birthing practices into a single suite of behaviours - such as the "six cleans"- may simplify policy and advocacy efforts. However, each clean practice has a unique set of determinants and understanding what drives or hinders the adoption of these individual practices is critical to designing more effective interventions to improve hygiene behaviours and neonatal and maternal health outcomes in LMIC. Current understanding in this regard remains limited. More theory-grounded formative research is required to understand motivators and social influences across different contexts.